Integrating Renewable Energy Technologies and Thermal Energy Storage to Support Building Trigeneration Systems: A Multicriteria Approach - Pina, Eduardo Antonio (Jornada de Jóvenes Investigadores del I3A, 2017)
The present work proposes a multi-objective optimization model to determine the optimal configuration and operation of trigeneration systems including renewable energy technologies (RET) and thermal energy storage (TES). The model minimises the total annual cost and CO2 emissions. Trade-off solutions between both objectives were obtained and different configurations were analysed.